Pendampingan Peningkatan Kompetensi Guru Akuntansi Kabupaten Wonosobo dalam Pengelolaan Keuangan Desa Melalui Aplikasi Siskeudes: Assistance in Enhancing Accounting Teachers' Competence in Wonosobo Regency in Village Financial Management Through the Siskeudes Application - Widayati, Ani; Wibawa, Eka Ary; Hakim, Arif Rahman; Nurrahman, Arief (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Transparent and accountable village financial management is a crucial pillar of good village governance. In Wonosobo Regency, there is an increasing need to enhance the competence of accounting teachers in village financial management using the Village Financial System Application (Siskeudes) to support the successful implementation of this policy. This community service activity aims to assist accounting teachers in Wonosobo Regency in understanding and applying village financial management through the Siskeudes Application. The methods employed include training, hands-on practice, and participant competency evaluation. The results of the activity indicate that this assistance has successfully improved the understanding and skills of accounting teachers in managing village finances by relevant laws and regulations. With this increase in competence, accounting teachers are expected to be able to teach village financial management to students more effectively and encourage active involvement in village financial oversight in the future. This service contributes to strengthening a more accountable village financial governance system in Wonosobo Regency.